2022
DOI: 10.1093/sleep/zsac007
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized, placebo-controlled trial of suvorexant for the treatment of vasomotor symptom-associated insomnia disorder in midlife women

Abstract: Study Objectives The neuropeptide orexin promotes wakefulness, modulates thermoregulation, increases after menopause, and is normalized in women receiving estrogen therapy, suggesting a role for orexin antagonism as a treatment for vasomotor symptom (VMS)-associated insomnia disorder. We tested the efficacy of the dual orexin receptor antagonist suvorexant for chronic insomnia related to nighttime VMS. Methods In a double-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Most of the studies have been conducted on suvorexant, also with objective methods (PSG), and on large series of patients, showing a remarkable efficacy of this drug in the treatment of insomnia. This effect was seen in both sexes, and suvorexant is currently the only DORA for which the efficacy has also been evaluated in menopause, 166 in older people, 169 and in adolescence. 172 Another very important property of suvorexant is the apparent absence of side effects on respiratory parameters during sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies have been conducted on suvorexant, also with objective methods (PSG), and on large series of patients, showing a remarkable efficacy of this drug in the treatment of insomnia. This effect was seen in both sexes, and suvorexant is currently the only DORA for which the efficacy has also been evaluated in menopause, 166 in older people, 169 and in adolescence. 172 Another very important property of suvorexant is the apparent absence of side effects on respiratory parameters during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia is often associated with other medical conditions and shows a considerable individual variability 4 in terms of clinical characteristics, sleep architecture, and comorbidities. 33 , 227 , 228 The orexin receptor antagonists have also been shown to afford an improvement in PSG parameters, sleepiness, and sleep quality, with differences related to the patient characteristics: some DORAs seem to have a good efficacy in the older subject or adolescent population 169 , 172 or in postmenopausal women, 166 whereas SORAs have been found effective in psychiatric patients. 218 , 229 , 230 Therefore, these drugs offer interesting perspectives for a targeted and personalized approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insomnia patients could use anxiolytics. Also, specific medications, like suvorexant, a drug that acts in the orexin neurotransmitter in the hypothalamus to regulate the sleep-arousal cycle, according to Rahman in 2022 [64].…”
Section: Therapeutic Aspectsmentioning
confidence: 99%
“…25 Recent findings demonstrated that the DORA suvorexant may be effective as a treatment of hot flash-associated insomnia in midlife women; however, the study duration was limited to 4 weeks. 26 The DORA lemborexant (LEM) is approved in several countries for the treatment for adults with insomnia. LEM is a competitive antagonist at orexin receptor types 1 and 2 and is thought to reduce wakefulness by attenuating orexin-mediated wake drive.…”
mentioning
confidence: 99%